Effect of Organic Zinc Coating Layers on Steel Corrosion Behaviour - Engku Norfatima, Engku Dahalan; Azizul Helmi, Sofian; Arman, Abdullah; Norhazilan, Md Noor; Abdul Halim Hadi, Che Mohammad Yahya (AENSI Publishing, 2016)
Throughout proper protection, preservation of metals in their pure form can be achieved. One of the possible methods is protection by organic zinc coating. This study was to compare the corrosion behaviour with different layers of coating between formulated organic zinc coating and commercialized spray. The pigment volume concentration (PVC) was diversified to 10, 20 and 30% with different layers of coating. The corrosion behaviour of coated sample was tested by using potentiostat. The results of polarization measurement show that the linear polarization resistance was significantly influencedby the pigment content and the layers of coating. The lowest corrosion rates for formulated organic zinc coating and commercialized spray were 0.00018 and 0.0062 mm/yr respectively, both from 5 layers of coating. 5 layers of coating give a better protection towards corrosion in corrosive environment.